(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
Labour migration in rural communities in Nigeria significantly impacts agricultural productivity and food security, particularly for cassava, a staple crop. This study examines the effects of labour migration on cassava productivity among farmers in Ekiti Local Government, Kwara State, Nigeria. A multi-stage sampling procedure was used to obtain 100 cassava farmers. Data collection employed structured questionnaires, with descriptive statistics and logistic regression analysis used to determine socioeconomic characteristics and predict labour migration. Descriptive statistics reveal an average household head age of 46.34 years (SD = 10.795), household size of 5 members (SD = 1.268), education level of 2.22 (SD = 1.834), and farming experience of 20.50 years (SD = 9.125). Average annual income is ₦2,323,597.01 (SD =₦1,043,094). These demographics indicate an aging farming population, limited education, and moderate economic stability. Logit regression analysis yields a strong model fit (χ2 = 80.250, p < 0.001) and accurately classifies 74.0% of cases. Extension services (β = 4.167, p < 0.05), remittances (β = 0.000, p < 0.05), and credit access (β = -4.876, p < 0.05) significantly predict labour migration. Demographic factors do not exhibit statistical significance. The study concludes that labour migration adversely affects cassava productivity among farmers in the study area. Therefore, policy interventions are recommended to enhance farmers’ quality of life, productivity, and income to mitigate labour migration’s adverse effects. This includes improving access to credit, extension services, and market information, providing basic amenities, and empowering farmers through income-increasing programs.